An investigation on Karakul ewes of the nutritional requirements during pregnancy and the effect of flushing and pregnant mare serum on reproductive performance - Klein, Werner Geoffrey (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- Universityof Stellenbosch, 1972.